Technical Perspective: A Chilly Sense of Security. - Anderson, Ross (Communications of the ACM, 2009)
The article discusses another article in the issue, "Lest We Remember: Cold-Boot Attacks on Encryption Keys," by J. Alex Halderman and others, which examines the manner in which security software is written and tested. Numerous systems rely on a master key being kept secret, the author states. Topics of discussion include laptop encryption software and protecting disk files kept in RAM (Random-Access Memory).